Standardization of Antiphospholipid Antibody Testing—Historical Perspectives and Ongoing Initiatives - Willis, Rohan; Lakos, Gabriella; Harris, E. Nigel (Seminars in Thrombosis and Hemostasis, 2014)
The measurement of antiphospholipid antibodies (aPL) has been an important aspect of antiphospholipid syndrome (APS) characterization since the disease was first described in the 1980s. Despite significant efforts geared toward the standardization of immunoassays that measure anticardiolipin antibodies and anti-β2-glycoprotein I spanning three decades, there are still reports of significant interassay and interlaboratory variation in the results of these assays. At the recent 13th International Congress on Antiphospholipid Antibodies (APLA 2010, April 13–16, 2010, Galveston, TX), a task force composed of internationally recognized experts in the field of APS was formed to address these issues. In this review, we discuss approaches that have been used in the past to achieve harmonization among aPL immunoassays as well as the ongoing efforts of the APLA task force. Our review also highlights the importance of cutoff determination in aPL assays and the clinical significance of positive aPL results of varying magnitudes.
Keywords: anticardiolipin antibodies; antiphospholipid antibodies; anti-β2 glycoprotein I antibodies; standardization